Mastering your fellowship: Part 1, 2022 - Klaus B. von Pressentin; Mergan Naidoo; Gert Marincowitz; Tasleem Ras (South African Family Practice)
The series, ‘Mastering your Fellowship’, provides examples of the different question formats encountered in the written and clinical examinations, that is, Part A of the Fellowship of the College of Family Physicians South Africa (FCFP SA) examination. The series is aimed at helping family medicine registrars (and their supervisors) prepare for this examination.